JURIDICAL ANALYSIS OF THE DISPARITY OF JUDGES' DECISIONS TO DRUG OFFENDERS IN THE SAME CASE (CASE STUDY OF EAST JAKARTA DISTRICT COURT DECISION NUMBER 334/PID.SUS/2022/PN.JKT.TIM, 335/PID.SUS/2022/PN.JKT.TIM, 336/PID.SUS/2022/PN.JKT.TIM, 337/PID.SUS/2022 - Trianingsih, Retno Sella (LPPM, Universitas Muhammadiyah Riau, 2024)
The imposition of sentences in cases charged under the same Article often results in differences between judges. As a maritime country, Indonesia is a heaven for the circulation of narcotics and other illegal drugs, primarily transported through sea routes. Disparities in criminal handling of narcotics cases persist, leading to variations in sentencing (sentencing disparities). The research problem is to identify the causes of disparities in judges' decisions for perpetrators of narcotics crimes in similar cases and to explore efforts to minimize these disparities. This study aims to analyze the causes of sentencing disparities among judges for perpetrators of narcotics crimes in similar cases and examine efforts to minimize such disparities. The research method employed is a normative legal research method. . Based on the research findings, criminal disparities in narcotics cases are caused by both juridical and substantial factors, particularly judicial independence. The freedom of judges in delivering sentences can result in sentencing disparities influenced by emotions, beliefs, and substantial factors such as age, background, religion, and the defendant's attitude. Efforts to minimize sentencing disparities can be achieved through the creation of standardized sentencing guidelines, providing clear limitations to judges.